Startup-AYUSH Portal - Chandra Sekhar Chauhan,; Shailendra Chaurasiya,; Harshvardhan Tiwary,; Mahesh Yadav, (International Journal of Scientific Research in Science and Technology, 2024)
The Startup AYUSH Portal is a pioneering initiative to transform the AYUSH ecosystem. It acts as a key hub and brings together startups, investors, incubators, accelerators, government agencies and the public. This innovative platform fosters collaboration, knowledge sharing, and growth in integrated healthcare. With the growing global interest in holistic medical and wellness practices, this platform serves as a dynamic and comprehensive hub for all stakeholders in the AYUSH ecosystem. The core of the portal is to facilitate seamless interaction and collaboration between startups, investors, incubators, accelerators, government agencies and the public. It provides a user-friendly interface that allows startups to showcase innovative AYUSH-related products and services, while investors explore investment opportunities in growing sectors. AYUSH Startup Portal is a key solution that will revolutionize the AYUSH startup industry. Startups can benefit from shared workspaces where they can showcase their AYUSH-related products and services. Investors have access to a rich pool of investment opportunities. Mentorship programs empower startups under the guidance of seasoned professionals. Our extensive resource center provides important information, regulatory updates and financing options. Key to our success are a variety of features, including collaborative workspaces, mentoring opportunities, abundant resources, and a global networking environment. Users can access the latest regulatory information, participate in virtual events and webinars, and engage with expert mentors. Government agencies can disseminate important policy updates by creating a regulatory environment conducive to AYUSH innovation. In a world where holistic health and wellness is gaining momentum, the AYUSH Startup Portal is a catalyst for advancement, unity and knowledge sharing within the AYUSH startup community, ultimately contributing to the growth of this important sector.
Keywords: Startup AYUSH portal; holistic healthcare; AYUSH ecosystem; Collaboration; Growth; Innovation; Investment Opportunities; Mentorship; Funding Options; Virtual Events; Global Networking